The anesthetic effect of AMSA technique for maxillary primary teeth - كابر نور; رسلان نبيه (Latakia University Journal -Medical Sciences Series, 2023)
Objective: Comparison the effectiveness of the AMSA technique in buccal tissue anesthesia with infiltration injection Materials and Methods: This randomized clinical study included 20 children. Each child received randomly the infiltration injection and the AMSA injection using lidocaine over two sessions. Anesthesia efficacy was assessed subjectively using the Wong-Baker Faces Pain Scale (WBF) Results: The AMSA injection showed significantly less pain compared to the infiltration injection when placing the rubber dam, according to the self-report pain scale. Conclusion: The AMSA injection is more effective than the infiltration injection in anesthetizing buccal tissues. Keywords: Infiltration, AMSA, insulin syringe.